2016
DOI: 10.1074/jbc.m116.724443
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Characterization of Inhibitory Synapses Using a Novel pHluorin-tagged γ-Aminobutyric Acid Receptor, Type A (GABAA), α2 Subunit Knock-in Mouse

Abstract: The accumulation of ␥-aminobutyric acid receptors (GABA A Rs) at the appropriate postsynaptic sites is critical for determining the efficacy of fast inhibitory neurotransmission. Although we know that the majority of synaptic GABA A R subtypes are assembled from ␣1-3, ␤, and ␥2 subunits, our understanding of how neurons facilitate their targeting to and stabilization at inhibitory synapses is rudimentary. To address these issues, we have created knock-in mice in which the pH-sensitive green fluorescent protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 55 publications
(44 reference statements)
3
60
1
Order By: Relevance
“…Comparing this approach to prior reports of the iPSD using affinity purification(1921), iBioID offers important advantages. Nearly all proteins previously reported to exist at the iPSD were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing this approach to prior reports of the iPSD using affinity purification(1921), iBioID offers important advantages. Nearly all proteins previously reported to exist at the iPSD were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Further identification of NL interactors and reconstitution of native NL-containing complexes at synapses may ultimately provide a unifying model relating synapse development, synaptic adhesion and neurotransmitter receptor localization. During revision of this manuscript, 174 proteins including LH4 were reported in immunoprecipitants of GFP-tagged α2-containing GABA A R complexes (Nakamura et al, 2016). Among these proteins, 7 proteins (Cul1, Ephexin, KCTD12, Mfn2, mGluR5, PAK5/7) were confirmed as potential direct interactors using a GST pulldown experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a recent proteomic characterization of inhibitory synapses identified novel GABA A R‐associated proteins and showed that the inhibitory postsynaptic densities are more complex than originally thought (Nakamura et al . ). Although the morphology and molecular composition of GABAergic synapses is very different from that observed in excitatory synapses, the main organization principles are conserved to a large extent.…”
Section: The Gabaergic Synapsesmentioning
confidence: 97%
“…) (see also Nakamura et al . ). Additional studies allowed the identification of gephyrin interaction motifs in the homologous regions of α1 and α3 (Maric et al .…”
Section: The Gabaergic Synapsesmentioning
confidence: 97%